Psychoeducation of Healthy Dating to Reduce the Risk of Sexual Violence in Female Street Children - Sri Kushartati, Dessy Pranungsari Koentjoro (Universitas Ahmad Dahlan, 2014)
Abstract This study was conducted to determine whether psychoeducation of healthy dating can reduce the risk of sexual violence in female adolescents of street children community. Subjects in this study were 8 adolescents of street children community of City North Square of Yogyakarta. The study used one group pretest-posttest design and follow up. The results of Wilcoxon test showed that there is no significant difference between the scores of sexual violence before psychoeducational healthy dating (pretest) and after (post-test) with the Z number of -1.420 and p value of 0.156 (p> 0.05), and the decrease of the mean score was 4.44. Likewise, there was no difference between the scores of sexual assault after courting healthy psychoeducation (posttest) and during follow-up with the Z number of -1.612 and p = 0.107 (p> 0.05) and the decrease of the mean score was 4. However, there were significant differences between the scores of sexual violence before (pretest) and follow-up with z = -2.103 and p = 0.035 (p <0.05), and the decrease of the mean score was 8.44 which indicated that the application of a psychoeducational healthy dating could reduce the risk of sexual violence of girls in street children community, but it needed 1 month to be applied in the form of healthy dating behavior.Keywords: psychoeducation of healthy dating, sexual violence, street children.